2018
DOI: 10.1111/agec.12453
|View full text |Cite
|
Sign up to set email alerts
|

Changing gender roles in agriculture? Evidence from 20 years of data in Ghana

Abstract: Many stylized facts about women in agriculture have been repeated for decades. Did nothing really change? Is some of this conventional wisdom simply maintained over time, or has it always been inaccurate? We use four rounds of cross-sectional data from Ghana to assess some of the facts and to evaluate whether gender patterns have changed over time. We focus on five main themes: land, cropping patterns, market participation, agricultural inputs, and employment. We add to the literature by showing new facts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…In many African smallholder farming households, men and women have different workloads and duties (Arora, 2015;Blackden & Wodon, 2006;Quisumbing et al, 1995). For example, ploughing tends to be done relatively more by men and weeding and processing by women (Alesina, 2011;Baanante et al, 1999); however, such gender roles can clearly vary across space and time (Lambrecht et al, 2017) and have also been questioned (Palacios-Lopez et al, 2017).…”
Section: Background and Research Hypothesesmentioning
confidence: 99%
“…In many African smallholder farming households, men and women have different workloads and duties (Arora, 2015;Blackden & Wodon, 2006;Quisumbing et al, 1995). For example, ploughing tends to be done relatively more by men and weeding and processing by women (Alesina, 2011;Baanante et al, 1999); however, such gender roles can clearly vary across space and time (Lambrecht et al, 2017) and have also been questioned (Palacios-Lopez et al, 2017).…”
Section: Background and Research Hypothesesmentioning
confidence: 99%
“…FAO (2011) further emphasized that women's contribution to agricultural and food production is significant but cannot be detailed as agriculture is a family venture and involves a range of resources and inputs that cannot be classified by gender. However, this burden has been decreasing through time as the participation of women in agricultural and non-agricultural employment had been increasing (Ghosh and Ghosh, 2014;Lambrecht et al, 2017). Akire et.…”
Section: Resultsmentioning
confidence: 99%
“…As such, these interventions can inadvertently propagate vulnerability and inequity in adaptive capacity rather than reduce it. For example, in the case of agricultural interventions, men or maleheaded households are much more likely to adopt improved seeds, which are largely promoted to both increase household crop productivity as well as to help households cultivate climate-resilient crops (Uduji and Okolo-Obasi 2018, Fisher and Kandiwa 2014, O'Brien et al 2016, Theriault et al 2017, Lambrecht et al 2018. Women and men also often engage in different forest harvesting activities, and when men are often the main voices in forest management programs like REDD+ this can impact women's vulnerability by reducing their capacity to benefit from forest resources (Devkota and Mustalahti 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies from East and West Africa have found that men, male-headed households, and households with a higher proportion of men were more likely than women, female-headed households, and households with a higher proportion of women to participate in programs that promote the use of fertilizer (Chen et al 2011, Fisher and Kandiwa 2014, Karamba and Winters 2015, Theriault et al 2017, Lambrecht et al 2018. Particular barriers to women's use of fertilizer include lack of capital, credit, and equipment, as fertilizer is typically expensive.…”
Section: Agricultural Technology Promotionmentioning
confidence: 99%
See 1 more Smart Citation